The evolution of scientific approaches to the study of political indoctrination: a conceptual analysis (Journal of Philosophy Culture and Political Science, 2026)
The article provides a conceptual analysis of scientific approaches to the study of political indoctrination. To overcome terminological fragmentation and develop a comprehensive understanding of this phenomenon, the authors employ four key approaches: institutional, substantial, sociological, and teleological. The study reveals that political indoctrination is a multilayered process where ideology intertwines with emotions, culture and institutional rituals. The authors conclude that the strength of an ideology is determined not by the sheer efficiency of indoctrination, but by the regime's ability to integrate it into everyday practices. Thus, political control through indoctrination is viewed not as a monolithic strategy, but as a dynamic process of adaptation of various institutions, including religious associations, to the political landscape.Key words: indoctrination, ideology, political control, propaganda.